2011
DOI: 10.1038/nn.2975
|View full text |Cite|
|
Sign up to set email alerts
|

Nictation, a dispersal behavior of the nematode Caenorhabditis elegans, is regulated by IL2 neurons

Abstract: Many nematodes show a stage-specific behavior called nictation in which a worm stands on its tail and waves its head in three dimensions. Here we show that nictation is a dispersal behavior regulated by a specific set of neurons, the IL2 cells, in C. elegans. We established assays for nictation and showed that cholinergic transmission was required for nictation. Cell type-specific rescue experiments and genetic ablation experiments revealed that the IL2 ciliated head neurons were essential for nictation. Intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
220
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(229 citation statements)
references
References 42 publications
9
220
0
Order By: Relevance
“…We turned to the six IL2 sensory neurons that are involved in nictation behavior (Lee et al, 2012). The IL2 neurons express unc-86 throughout their lifetime and have been inferred to be cholinergic (Lee et al, 2012). We corroborated the cholinergic identity of the IL2s by finding that reporter fusions to the unc-17/cha-1 locus and to the choline reuptake transporter cho-1 are expressed in IL2 neurons (Fig.…”
Section: Both Ttx-3 and Unc-86 Single Mutants Also Show Defects In Domentioning
confidence: 65%
See 1 more Smart Citation
“…We turned to the six IL2 sensory neurons that are involved in nictation behavior (Lee et al, 2012). The IL2 neurons express unc-86 throughout their lifetime and have been inferred to be cholinergic (Lee et al, 2012). We corroborated the cholinergic identity of the IL2s by finding that reporter fusions to the unc-17/cha-1 locus and to the choline reuptake transporter cho-1 are expressed in IL2 neurons (Fig.…”
Section: Both Ttx-3 and Unc-86 Single Mutants Also Show Defects In Domentioning
confidence: 65%
“…We asked whether unc-86 might affect the terminal differentiation program of neurons that use yet another neurotransmitter system. We turned to the six IL2 sensory neurons that are involved in nictation behavior (Lee et al, 2012). The IL2 neurons express unc-86 throughout their lifetime and have been inferred to be cholinergic (Lee et al, 2012).…”
Section: Both Ttx-3 and Unc-86 Single Mutants Also Show Defects In Domentioning
confidence: 99%
“…Although the existence of graviperception mechanisms in C. elegans has been reported (Beckingham et al, 2005), there is no information about where and how gravity is perceived in nematodes. Lee et al (Lee et al, 2012) found that nictation is regulated by IL2 neurons in C. elegans. Thus, IL2 neurons may be related to graviperception in nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Nictation is thought to be a dispersal behavior unique to dauer larvae. Nictation cannot occur without a substrate such as mold or gauze and thus will not occur on standard, uncontaminated plates (Cassada and Russell, 1975; Lee et al, 2012). Dauer larvae on the surface of a plate are often quiescent, and can appear still and rodlike.…”
Section: Isolating Dauer Larvaementioning
confidence: 99%
“…Dauer larvae on the surface of a plate are often quiescent, and can appear still and rodlike. They do however move quickly in response to stimuli (Cassada and Russell, 1975; Lee et al, 2012). …”
Section: Isolating Dauer Larvaementioning
confidence: 99%